2018
DOI: 10.1136/bmjopen-2017-021425
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and discourses about breast cancer prevention among immigrant women in Spain: a qualitative study

Abstract: ObjectivesTo identify knowledge, barriers and discourses about breast cancer screening in Spain among female immigrants from low-income countries and native Spanish women from a low socioeconomic class.DesignQualitative interview study with thematic analysis interpreted using cultural mediators.SettingMallorca, Spain.ParticipantsThirty-six in-depth interviews, using cultural mediators, of immigrant women living in Mallorca who were 50–69 years old and were from Maghreb, Sub-Saharan Africa, Eastern Europe, Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Other studies also show consistent findings; it has been observed that a lack of time due to work responsibilities is a barrier associated with preventative breast cancer screening among populations of immigrant women in Spain. This is due to the fact that these immigrant women had strict job schedules with job security concerns, resulting in a reluctance to take time off work [ 47 ]. Due to these time constraints among immigrant women, it is imperative that future interventions consider the work schedules and availability of this target population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also show consistent findings; it has been observed that a lack of time due to work responsibilities is a barrier associated with preventative breast cancer screening among populations of immigrant women in Spain. This is due to the fact that these immigrant women had strict job schedules with job security concerns, resulting in a reluctance to take time off work [ 47 ]. Due to these time constraints among immigrant women, it is imperative that future interventions consider the work schedules and availability of this target population.…”
Section: Discussionmentioning
confidence: 99%
“…Some women expressed that women from their native countries sometimes are dependent on their husbands to accompany them to the screening centre and it can be difficult for these women to coordinate their screening appointments with their husbands’ schedules (Bhargava, Hofvind, & Moen, 2019). Women expressed prioritizing work, worrying about money and job security and having difficulties taking time off for appointments (March et al, 2018; Suwankhong & Liamputtong, 2018). A fear of discovering that they developed cancer and had to stop working and would not be able to provide for their families was also expressed (March et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Women expressed prioritizing work, worrying about money and job security and having difficulties taking time off for appointments (March et al, 2018; Suwankhong & Liamputtong, 2018). A fear of discovering that they developed cancer and had to stop working and would not be able to provide for their families was also expressed (March et al, 2018). Some women expressed that mammography is a very expensive procedure in their native country and therefore they never went, other women had their mammograms performed in their native countries when they went back to visit (March et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, however, we should not ignore the possible persisting cultural stigma around the word “cancer” and “palliative care” in specific. Although cancer, thanks to the many medical improvements, is becoming a chronic disease which can be managed over time, and is thus less stigmatized; studies seem to suggest that in Eastern Europe the word is often still avoided because it is considered as a source of a certain disgrace [ 19 , 31 ]. Unlike for cancer, the stigma surrounding PC seems to be a more global phenomenon which has been frequently reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%